Dopamine-Related Genes Moderate the Association Between Family Environment and Executive Function Following Pediatric Traumatic Brain Injury: An Exploratory Study. Issue 4 (July 2020) - Smith-Paine, Julia; Fisher, Allison P.; Wade, Shari L.; Zhang, Nanhua; Zang, Huaiyu; Martin, Lisa J.; Yeates, Keith Owen; Taylor, H. Gerry; Kurowski, Brad G.
Abstract : Objective: This study examined whether carrying dopamine-related "risk" genes—either the dopamine transporter (DAT1) 10-repeat allele or dopamine receptor-4 (DRD4) 7-repeat allele—moderated the association of family environment and executive function (EF) following traumatic brain injury (TBI) in early childhood. Methods: Caregivers of children with TBI or orthopedic injury (OI) completed the Behavior Rating Inventory of Executive Function (BRIEF) at postinjury visits. General linear models examined gene by environment interactions as moderators of the effects of TBI on EF at 12 months and 7 years postinjury. Results: At 12 months, we did not find any significant gene by environment interactions. At 7 years, we found a significant 3-way interaction among combined carrier status, level of permissive parenting, and injury type. For children exposed to more optimal parenting, carriers of DAT1 and/or DRD4 risk alleles with TBI showed significantly worse parent-reported EF than carriers with OI. In those with less optimal parenting, carriers and noncarriers with TBI, as well as carriers with OI, showed significantly worse parent-reported EF than noncarriers with OI, with medium to large effect sizes. Conclusions: The findings highlight the importance of considering polygenetic and environmental factors in future studies of recovery following TBI and other injuries in childhood.